2004
DOI: 10.1136/bjsm.2002.003806
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the sports safety policies and practices of community sports clubs during training and competition in northern Sydney, Australia

Abstract: Objectives:To compare the safety policies and practices reported to be adopted during training and competition by community sports clubs in northern Sydney, Australia.Methods:This cross sectional study involved face to face interviews, using an 81 item extensively validated questionnaire, with representatives of 163 community netball, rugby league, rugby union, and soccer clubs (response rate 85%). The study was undertaken during the winter sports season of 2000. Two separate 14 item scales were developed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Previous studies have suggested that adequate maintenance of sport ground safety in local sports clubs is more likely in the presence of a governing body policy or guidelines (Donaldson, Forero, Finch, & Hill, 2004;Swan, Otago, Finch, & Warren, 2009). Therefore, it was hypothesised that municipality offices in municipalities that explicitly mentioned sports safety in policy documents would be more likely to perform frequent inspections and involve sports clubs in the inspection of sports grounds.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have suggested that adequate maintenance of sport ground safety in local sports clubs is more likely in the presence of a governing body policy or guidelines (Donaldson, Forero, Finch, & Hill, 2004;Swan, Otago, Finch, & Warren, 2009). Therefore, it was hypothesised that municipality offices in municipalities that explicitly mentioned sports safety in policy documents would be more likely to perform frequent inspections and involve sports clubs in the inspection of sports grounds.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have previously investigated community initiatives to reduce safety hazards at local sports facilities (Donaldson, Forero, Finch, & Hill, 2004). This study therefore first describes the existence of explicit sports safety policies in a set of Swedish municipalities with and without allpurpose health or safety promotion programmes.…”
Section: Introductionmentioning
confidence: 99%
“…An audit of 163 community sports clubs (rugby, netball and soccer) showed that the implementation of safety policies was low, especially during practice 28. Based on these results, a risk management training module was developed, consisting of three 2 h training sessions, using problem-centred learning strategies.…”
Section: Discussionmentioning
confidence: 99%
“…SafeClub was developed in response to a survey that found that few community soccer clubs adopted a strategic approach to safety or had the infrastructure to implement sustainable injury prevention initiatives 27. Additional informal consultations with regional sports associations and community clubs also suggested that the safety issues of concern varied significantly from club to club depending on the club’s size, facilities, human resources, location, and player and spectator characteristics.…”
Section: Methodsmentioning
confidence: 99%